The influence of website quality dimensions on electronic customer satisfaction : a study of the hotel industry in Terengganu - Tasneem Shahid
The internet has become a crucial business platform which is commonly known as ecommerce for trading, distributing, selling and promoting products or services. In the tourism industry like hotels, customers are more demanding and tech savvy. Since theonline market is growing and becoming more and more competitive, hotels are investigating an effective way to keep customers making reservation directly through the hotel's own website. Previous studies showed that Malaysian hotel industry experienced huge fluctuations due to poor communication and technology. Therefore, this study examines the influence ofwebsite quality dimensions namely user interface quality, information quality, security perception and notion of privacy on electronic customers' satisfaction toward the online hotel reservations for booking a room in starrated hotels in Terengganu. The study was based on a sample gathered from 350 customers from star-rated hotels in Terengganu. There are 21 star¬rated hotels involved in this study. The present study used a self-administered questionnaire and a stratified sampling approach. The data was analyzed by using Statistical Package for the Social Sciences (SPSS) version 21.0. The Multiple regression analysis was used to test the research hypotheses. The results showed that the information quality, the notion of privacy and the user interface quality were significantly related to electronic customers' satisfaction. However, the security perception was found not significantly related to electronic customers' satisfaction. The findings of this study provided insights to hoteliers with regard to the importance of deploying the information quality, the notion of privacy and the user interface quality with regard to their hotel website in order to increase customers' satisfaction. Furthermore, implications of the study findings, limitations and directions for future research are also discussed.